Lithic technology, chronology, and marine shells from Wadi Aghar, southern Jordan, and Initial Upper Paleolithic behaviors in the southern inland Levant. Issue 135 (October 2019) - Kadowaki, Seiji; Tamura, Toru; Sano, Katsuhiro; Kurozumi, Taiji; Maher, Lisa A.; Wakano, Joe Yuichiro; Omori, Takayuki; Kida, Risako; Hirose, Masato; Massadeh, Sate; Henry, Donald O.
Abstract: The Initial Upper Paleolithic (IUP) temporally overlaps with the range expansion of Homo sapiens populations in various parts of Eurasia and is often considered a key archaeological phase for investigating behavioral changes from the Middle Paleolithic. This paper reports upon new data from IUP occupations at Wadi Aghar, a rock shelter site in the southern Levant. In combining the results of radiometric dates and lithic analyses, we clarify the chronological and cultural position of Wadi Aghar assemblages in the Levantine IUP. As for the records about mobility, on-site activities, and resource procurement behaviors, we present analyses of lithic use-wear, tool-type composition, soil micromorphology, and marine shells. The lithic analyses and the optically stimulated luminescence (and subsidiary radiocarbon) dating of the Wadi Aghar materials suggest their chronocultural position in the IUP (45–40 ka for Layers C–D1; 39–36 ka for Layer B; possibly 50 ka for Layer D2), providing the southernmost location for the IUP in Eurasia. In the Levant, Wadi Aghar represents one of the few IUP sites in the inland areas. The results also indicate that the timing and technological sequences from the IUP to the following bladelet industries differed between the inland and coastal zones, likely reflecting geographically variable adaptive behaviors and/or cultural transmissions. One of the behavioral characteristics of IUP foragers at Wadi Aghar is the procurement of remote resources, represented by the transportation of marine shells from the Red Sea: Canarium fusiforme and Canarium cf. mutabile . Whether it was a direct procurement with increased mobility or a result of intergroup exchanges, it was not part of behavioral repertoires during the late MP in the same area. This can be understood as the expansion of resource procurement range, functioning as additional buffers from risk in the semiarid environments in the inland Levant.